The mood congruence memory effect: Differential recognition of sadness and joy words - G. Meilán, Juan José; Carro, Juan; Guerrero, Cristina; Carpi, Amparo; Gómez, Consuelo; Palmero, Francesc (Anales de Psicología / Annals of Psychology, 2012)
Studies on the mood congruence effect commonly used clinical samples of depressed people use affect induction programs introspective, and measure the memory with free recall tasks. We intend to verify this hypothesis induces two conflicting moods in 100 participants without pathology. The aim was to study the influence of mood on the recognition of words congruent with those moods. To induce affective states, we use the association of images and music with the dimension of sadness and joy. After they learned words related to the two emotional states. We found interaction effects between type of induced emotional state and recognition of emotional words in both latencies as indices of discrimination A ’. However, we found differences in the recognition depending on the mood. The mood congruence effect occurs in the processing of words in the category of sadness, but not in the words of the category of joy. These latencies are faster and higher rates of discrimination, regardless of the experimentally induced state.